Application of ethanol extracts of Tapinanthus dodoneifolius to inhibit annealed carbon corrosion in 2 M HCl and 3.5% NaCl solutions - Oguike, Raphael Shadai; Shibdawa, Abdullahi Mohammad; Tafida, Usman Ibrahim; Boryo, Doris Ezekiel Amin; Omizegba, Florence Ikwo (European Journal of Chemistry, 2017)
Protection effect of ethanol extracts of Tapinanthus dodoneifolius leaf (TD extracts) on corrosion of annealed carbon (FE164531) in 2 M HCl and 3.5% NaCl solution has been investigated by weight loss and electrochemical techniques. Surface morphology and elemental analysis was carried out on the corroded specimens using Scanning Electron Microscope/ Energy Dispersive X-ray Spectroscopy (SEM/EDS) to augment results obtained. The data obtained from weight loss revealed that the corrosion protection potentials of TD extract is temperature-concentration dependent. The effectiveness of protection against the corrosive environment increased with increasing extracts concentration but decreased with increased temperature. Electrochemical polarization data showed TD extracts suppressed both the cathodic and anodic processes on FE164531 specimen surface. Calculated thermodynamic parameters showed that TD extracts adsorption process was spontaneous with likely electrostatic interactions which propose physical adsorption, a phenomenon consistent with unfavorable adsorption with increasing experimental temperature. The elemental analysis data show the presence of TD extracts species on FE164531 surface supporting strong adsorption of the extracts on the metal surface while SEM showed lesser corroded surface in the presence of TD extracts.